2013
DOI: 10.1016/s0034-7094(13)70215-0
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Routine Testing in Low-risk Patients Undergoing Minor and Medium Surgical Procedures

Abstract: We found that preoperative additional tests are excessively ordered, even for young patients with low surgical risk, with little or no interference in perioperative management. Laboratory tests, besides generating high and unnecessary costs, are not good standardized screening instruments for diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, several studies including randomized clinical trials continue to show no difference in outcomes when comparing routine to no preoperative testing (Benarroch-Gampel et al 2012 ; Keay et al 2012 ; Schein et al 2000 ; Sheffield et al 2013 ). Finding changes in tests of clinically healthy or stable patients usually does not alter clinical management during the perioperative period (Soares Dde et al 2013 ). Instead, un-indicated investigations detect minor abnormalities of no clinical relevance which may be unsafe for patients causing unnecessary delay, further scrutiny of false positive or inconsequential findings, and cancellation of surgery and medico-legal liability if not addressed (Kumar and Srivastava 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies including randomized clinical trials continue to show no difference in outcomes when comparing routine to no preoperative testing (Benarroch-Gampel et al 2012 ; Keay et al 2012 ; Schein et al 2000 ; Sheffield et al 2013 ). Finding changes in tests of clinically healthy or stable patients usually does not alter clinical management during the perioperative period (Soares Dde et al 2013 ). Instead, un-indicated investigations detect minor abnormalities of no clinical relevance which may be unsafe for patients causing unnecessary delay, further scrutiny of false positive or inconsequential findings, and cancellation of surgery and medico-legal liability if not addressed (Kumar and Srivastava 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Onuoha et al ( 2014b ) in conjunction with the ASA conducted a survey of clinical anesthesiologists and results indicated that the utilization of low-value services are often driven by external factors other than patient safety such as the lack of control by anesthesiologists over preoperative testing, surgeon preference, patient preference or demand, medico-legal concerns, or postoperative needs. Additional predictors include facility preference, practice tradition, concerns about surgical delay or cancellation, institutional policies and procedures, and the lack of both clear guidelines or the awareness of current evidence with respect to preoperative testing (Benarroch-Gampel et al 2012 ; Brown and Brown 2011 ; Soares Dde et al 2013 ). In a survey of anesthesiologists, the most notable but modifiable challenge was the lack of communication and collaboration by all stakeholders involved in the perioperative care of the patient (Onuoha et al 2014b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pathological laboratory findings in otherwise healthy children is low. Furthermore, positive findings do not necessarily produce a change in anesthetic practice . Frequently, preoperative routine blood tests appear to be justified by legal, rather than medical, reasons…”
Section: Choosing Wisely In Pediatric Anesthesia: 10 Dos and Don′tsmentioning
confidence: 99%
“…We assume that a normal test value is set arbitrarily based on 95% confidence interval; therefore up to 5% of normal individuals may have a value outside of the reference interval. Moreover, if we consider that tests are independent of each other, then the greater the number the tests ordered, the greater the chance of obtaining a result outside of the reference interval in a healthy patient ( 4 ). Screening tests in an asymptomatic population should only be done in patients with a significant and prevalent condition.…”
Section: Introductionmentioning
confidence: 99%